Pasti uvedbe pravila poslovne odločitve (business judgment rule) v slovensko korporacijsko pravo - Podobnik, Klemen (Pravnik, 2016)
The paper critically examines the unsuccessful attempts to amend the corporate legislation in Slovenia in the ambit of managers' duty to care. The author then sketches out the amendment proponents' perception of the business judgment rule and the method and manner that were used in the attempt to codify it. The main thrust of the article is dedicated to the analysis of the development of the business judgment rule doctrine in the United States (its birthplace), whereby the author determines that (a) the doctrine's development is still ongoing and (b) there is no single uniform interpretation of the its meaning, both mainly due to the highly diverging perceptions of its ambit and reach by the Delaware courts. These facts are then used to question the validity of a somewhat sophistic and hasty enactment of the doctrine in Slovenia, which could lower an already dangerously low level of general deterrence function of damages for illegal directors' acts.
Keywords: gospodarske družbe; gospodarsko pravo; management; poslovne odločitve; presojanje; upravljanje; vodenje